Which is the best management for women with normal cervical cytologic findings despite positivity for non-16/18 high risk human papillomaviruses? - Wu, Ming; Ma, Xiaotong; Li, Huiyang; Li, Bijun; Wang, Chen; Fan, Xiangqin; Fan, Aiping; Xue, Fengxia (Frontiers in Public Health, 2022)
Women with a positive result to Human papillomavirus (HPV) test who have a normal cytology represents the predominant subgroup of patients in the screening population in the post-vaccination era. The distribution of HPV genotypes underwent a dramatic change attributable to the increasing HPV vaccination coverage. These changes have generated confusion about the proper management of women with normal cytology and non-HPV 16/18 infections as well as of women with persistent infections. Current recommendations include retesting or continued surveillance in the absence of infection by HPV 16/18. However, they are not always applicable everywhere. The capacity to implement genotyping or incorporate HPV 16/18 with some additional high-risk HPV types could be acceptable for the triage and management aimed to identify type-specific risks in this population; the generation of potential triage strategies for detecting high-grade cervical lesions, such as p16/Ki67 cytology assay, and other alternatives that incorporate genotyping with newer tests, could be taken into future considerations and changes on updating of guidelines. Current clinical managements are shifting to risk-based strategies, yet specific risk threshold in this population has not been established. Importantly, innovative triage testing needs to be evaluated in combination with primary screening and management. Furthermore, the opportunity still exists to coordinate HPV genotyping in combination with colposcopic characteristics to modify risk in this group, although this strategy is not being fully exploited. Hence, it is worth exploring how to provide a more personalized schedule by applying risk stratification efficiently, thereby improving the identification of precancer and cancer.